The Effect of adding roasted soybeans and Indigofera leaves on its digestibilities and milk production of Anglo Nubian does: Pengaruh Penambahan Biji Kedelai Sangrai dan Daun Indigofera pada Pakan Kambing Anglo Nubian Laktasi Terhadap Produksi Susu dan Kecernaannya - Hidayat, Hidayat; Akbarillah, Tris; Amrullah, Amir Husaini Karim (Buletin Peternakan Tropis, 2025)
This study was conducted  to evaluate the addition of roasted soybean seeds and Indigofera leaves to diet consisting of grass and tofu dregs on the consumption, digestibility and milk production of Anglo Nubian does. Four  Anglo Nubian does, mid-lactation, first parity, as Latin square experimental animals with 4 treatments in 4 experimental periods. The treatments are P0 as a control, in the form of  grass as much as 6 kg and concentrate (wet tofu dregs) as much as 6 kg, then P1 is a control diet plus 100 g of roasted soybeans, P 2 is a control diet plus 200 g of roasted soybeans, and P3 is a control diet plus 1000 g of fresh Indigofera leaves. Data were analyzed using variance and continued with the least significant difference test if there was a significant difference. The variables observed were the nutritional content of feed ingredients, nutrient consumption from the treatment feed used, and feed digestibility, as well as the average daily milk production. The results of the experiment showed that the average consumption of  grass nutrients was not significantly different between treatments (P>0.05), the average consumption of total dry matter  was significantly different (P<0.05). The total consumption of crude protein and total energy increased significantly (P<0.05). The average digestibility of feed nutrients was not significantly different (P>0.05). In general, the average daily milk production increased significantly (P<0.05). This study can be concluded that the addition of 200 g of roasted soybeans and 1000 g of Indigofera leaves  to diet of mid-lactation Anglo Nubian does can increase the average daily milk production